Mean Platelet Volume in Diabetic Retinopathy and its Association with Duration of Diabetes and Glycaemic Control in Type 2 Diabetics (Medical Forum Monthly, 2024)
Objective: To study the mean platelet volume (MPV) in diabetic retinopathy (DR) with special reference to duration of diabetes and glycaemic control (HbA1c) in type 2 diabetics (DM).Study Design: Case control studyPlace and Duration: This study was carried out at the Department of Medicine, Liaquat University Hospital Jamshoro, from March 2014 to December 2014.Materials and Methods: 100 subjects; comprising of 50 controls and 50 cases of DR were selected as per criteria and evaluated for study variables. Blood sample were collected in anticoagulant sterilized bottles for analysis of hematoanalyzer. Volunteers were requested to sign the informed consent proforma. Statistix 8.1 was used for data analysis. Pearson’s correlation (r), student t test and Chi square were used for data analysis. p≤0.05 was defined significant.Results: MPV values were found raised in DR subjects compared to controls i.e.; 11.7±3.2 fl versus 9.12±2.1 respectively (p <0.0001). MPV was positively correlated with HbA1c (r=0.740, p-value= 0.0001) and duration of DM (r=0.510, p=0.0001).Conclusion: The present study reports raised mean platelet volume was diabetic retinopathy which was positively correlated with HbA1c and duration of diabetes.